The Case for Cannabidiol-Integration of Eastern and Western Medical Traditions and the Promise for the Future: A Narrative Review and Commentary - Pressman, Peter; Hoeng, Julia; Padmindra, Pornchai; Warinhomhoun, Sakan; Hayes, Wallace (Pharmacognosy Reviews)
Our intent in the following narrative review and commentary is to underscore the importance of critically re-exploring ancient and enduring medical traditions. We support a view that rediscovering and augmenting the elements of the past, especially in the context of Eastern traditions, will inform and strengthen the global future. In the absence of the historical and multicultural perspective, it could be argued that we have become rather myopic or focused within discrete silos; we seem continually to re-invent the wheel in successively refined form, without truly evaluating foundations, traditions, and history of use. This situation suggests that technologically sophisticated investigators and clinicians are not necessarily aware of the full spectrum of the safety, efficacy, clinical indications, and guidelines for the use of many naturally sourced pharmacologic formulations with a remarkably long history of widespread use, and with implications for valuable and innovative drug development. We discuss Cannabidiol (CBD) as illustrative of such an opportunity.
Keywords: Cannabidiol; CBD; Eastern Medicine; Traditional Medicine; Integrative Medicine